The incremental cost of delivering PrEP as a bridge to ART for HIV serodiscordant couples in public HIV care clinics in Kenya - Irungu, EM; Sharma, M; Maronga, C; Mugo, N; Ngure, K; Celum, C; Barnabas, RV; Baeten, J; Heffron, R (Hindawi Limited, 2019)

(untitled)
Background. In 2016, the Kenyan Ministry of Health (MOH) released guidelines that recommend preexposure prophylaxis (PrEP) for persons with substantial ongoing HIV risk, including those in HIV serodiscordant partnerships. Estimates of the costs of delivering PrEP within Kenyan public health facilities are needed for planning for PrEP scale up. Methods. We estimated the incremental annual costs of providing PrEP to HIV uninfected partners as a time-limited “bridge” until the infected partner is virally suppressed on ART within HIV serodiscordant couples as part of routine clinic care in Thika, Kenya. Costs were collected from the Partners Demonstration Project, a prospective evaluation of integrated delivery of preexposure prophylaxis (PrEP) and antiretroviral therapy (ART) to high-risk HIV serodiscordant couples. We conducted time and motion studies to distinguish between activities related to research, routine clinical care, and PrEP delivery. Costs (2015 US dollars) were collected from the MOH perspective and divided into staff, transportation, equipment, supplies, buildings and overhead, and start-up. Results. PrEP related activities conducted during the screening, enrollment, and follow-up visits took an average of 13 minutes, 51 minutes, and 12 minutes, respectively. Assuming a staff structure of 3 counselors, 1 nurse, and 2 clinicians, we estimate that 3,178 couples can be screened, 1,444 couples offered PrEP and ART, and 6,138 couples followed up annually in an average HIV care clinic. Using costs incurred by the MOH for personnel, drug, and laboratory tests, we estimate that the incremental cost of offering PrEP to HIV uninfected partners within existing ART programs is $86.79 per couple per year. Personnel and PrEP medication made up the largest portion of the costs. We estimate that the total cost to Ministry of Health of delivering integrated PrEP and ART program in public health facilities is $250.19 per HIV serodiscordant couple per year. Conclusions. Time-limited provision of PrEP to the HIV uninfected partner within HIV serodiscordant couples can be an affordable delivery model implemented in HIV care programs in Kenya and similar settings. These costs can be used for budgetary planning and cost effectiveness analyses.